2022
DOI: 10.1002/wrna.1759
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of circular RNAs with advanced sequencing technologies in human complex diseases

Abstract: Circular RNAs (circRNAs) are one category of non‐coding RNAs that do not possess 5′ caps and 3′ free ends. Instead, they are derived in closed circle forms from pre‐mRNAs by a non‐canonical splicing mechanism named “back‐splicing.” CircRNAs were discovered four decades ago, initially called “scrambled exons.” Compared to linear RNAs, the expression levels of circRNAs are considerably lower, and it is challenging to identify circRNAs specifically. Thus, the biological relevance of circRNAs has been underappreci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 136 publications
0
4
0
Order By: Relevance
“…It is worth noting that other publications in the literature have reviewed different aspects of the computational tools for circRNA identification and its in silico functional characterization (see [ 51 , 71 , 139 ]). However, unlike other reviews, our work offers a more accessible description of the most popular tools for circRNA identification, including technical aspects, as well as a compilation of the most popular tools for its in silico characterization in order to obtain functional insights of their biological roles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth noting that other publications in the literature have reviewed different aspects of the computational tools for circRNA identification and its in silico functional characterization (see [ 51 , 71 , 139 ]). However, unlike other reviews, our work offers a more accessible description of the most popular tools for circRNA identification, including technical aspects, as well as a compilation of the most popular tools for its in silico characterization in order to obtain functional insights of their biological roles.…”
Section: Discussionmentioning
confidence: 99%
“…Ruan et al (2022) [ 71 ] presented a comprehensive overview of different experimental strategies for full-length sequencing splicing variants detection of circRNAs. The authors summarize various library preparation techniques that enrich the sample for circRNAs and pipeline analysis using Oxford Nanopore Technology (ONT) sequencing.…”
Section: Introductionmentioning
confidence: 99%
“…Profiling by sequencing has become much more accessible in recent years, given the development of efficient bioinformatic tools for detecting circRNAs, which have been thoroughly described elsewhere (Chen et al, 2021;Rebolledo et al, 2023;Ruan et al, 2023). The novel tools can use previously reposited single and paired read total RNA-seq datasets to detect circRNAs (Nguyen et al, 2021(Nguyen et al, , 2022).…”
Section: Sequencing's Growing Footprint In Profilingmentioning
confidence: 99%
“…Recent studies have revealed that the circular RNA molecules take part in numerous cellular activities like, Gene Expressions, Sponging of miRNAs, and Binding to proteins for the regulatory purposes to name a few [1][2][3][4][5][6][7][8][9][10]. As a matter of surprise, some of the circular RNAs have been found to be able to code for peptides/proteins having a variety of functionalities [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%